Is website interactivity beneficial for low involvement products? - Zotos, Yorgos; Tsiotsou, Rodoula H.; Palla, Polyxeni (My University, 2012)
Despite the central role of interactivity in the online media, the available literature provides conflicting findings. A stream of research supports the view that increased levels of interactivity in a web environment are positively related to effective advertising results such as formation of positive attitude toward the brand and increased pre-purchase intentions. However, another stream of studies posits that enhanced levels of interactivity are associated with negative effects on the online communication process such as limited process of the provided information. Therefore, the purpose of this study is to shed light in the above discrepancies and clarify the role of interactivity on online advertising effectiveness. The paper synthesizes the emerging Internet related and marketing literature in an effort to understand the way interactivity impacts advertising effectiveness for low involvement products. An experimental study is employed aiming at examining the influence of various interactivity levels (high, medium, low) on website effectiveness expressed the attitude towards the website, intention to revisit the website and pre-purchase behavior. Multivariate analysis was employed and released a number of interesting findings. The most remarkable finding is that the medium interactivity in a website of a low involvement product is the most effective one, as compared to the low and high interactive. In particular, medium interactivity in a website elicits most positive attitudes, greatest intention to revisit the website and highest pre-purchase behavior.
Keywords: Interactivity; Online media; Internet; Online advertising